Tales From Three 18th Century Eruptions to Understand Past and Present Behaviour of Etna - Corsaro, Rosa Anna; Branca, Stefano; De Beni, Emanuela; Tanguy, Jean-Claude (Frontiers in Earth Science, 2021)
The structure of an active volcano is highly dependent on the interplay between the geodynamic context, the tectonic assessment as well as the magmatic processes in the plumbing system. This complex scenario, widely explored at Etna during the last 40 years, is nevertheless incomplete for the recent historical activity. In 1763 two eruptions occurred along the west flank of the volcano. There, an eruption started on 6th February and formed the scoria cone of Mt. Nuovo and a roughly 4-km-long lava flow field. Another small scoria cone, known as Mt. Mezza Luna, is not dated in historical sources. It is located just 1 km eastward of Mt. Nuovo and produced a 700 m long flow field. We focused on the activity of Mts. Nuovo and Mezza Luna for several reasons. First, the old geological maps and volcanological catalogues indicate that Mt. Mezza Luna and Mt. Nuovo cones were formed during the same eruption, while historical sources described Mt. Nuovo’s activity as producing a single scoria cone and do not give information about the formation of Mt. Mezza Luna. Second, petrologic studies highlight that the products of Mt. Mezza Luna are similar to the sub-aphyric Etna basalts; they preserve a composition relatively close to Etna primitive magma which were also erupted in 1763, during La Montagnola flank eruption, which took place along the South Rift of the volcano. Third, the two scoria cones built up along the so-called West Rift of Etna, which represents one of the main magma-ascent zones of the volcano. We applied a multidisciplinary approach that could prove useful for other volcanoes whose past activity is still to be reconstructed. Critical reviews of historical records, new field surveys, petrochemical analyses and petrologic modelling of the Mts. Nuovo and Mezza Luna eruptions have been integrated with literature data. The results allowed improving the stratigraphic record of historical eruptions reported in the Mount Etna Geological map, modelling the sub-volcanic magmatic processes responsible for magma differentiation, and evidencing recurrent mechanisms of magma transfer at Etna. Indeed, the intrusion of a deep primitive magma along the South Rift is often associated with the activation of other rift zones that erupt residual magma stored in the shallow plumbing system.